Healthcare Professionals’ Knowledge of Pharmacogenetics and Attitudes Towards Antimicrobial Utilization in Zambia: Implications for a Precision Medicine Approach to Reducing Antimicrobial Resistance - Mufwambi, Webrod; Stingl, Julia; Masimirembwa, Collen; Manasa, Justen; Nhachi, Charles; Stadler, Nadina; Mwila, Chiluba; Kalungia, Aubrey Chichonyi; Mukosha, Moses; Mutiti, Chenai S.; Kamoto, Alfred; Kaonga, Patrick; et al. (Frontiers in Pharmacology, 2021)
Introduction: Sub-Saharan Africa (SSA) and other low- and middle- income countries (LMICs) have the highest rates of antimicrobial resistance (AMR) driven by high rates of antimicrobial utilisation. This is a concern with AMR increasing morbidity, mortality and costs. Pharmacogenetics (PGx) and precision medicine are emerging approaches to combat AMR. Consequently as a first step there is a need to assess AMR knowledge and attitudes, and knowledge of PGx among healthcare professionals in a SSA country, and use the findings to guide future interventions. Methodology: Descriptive cross-sectional study involving 304 healthcare professionals at tertiary hospitals in Lusaka, Zambia. Structural Equation Modelling (SEM) was used to analyse relationships among latent variables. Results: Overall correctness of answers about AMR among healthcare professionals was 60.4% (7/11). Knowledge on pharmacogenetics was low (38%). SEM showed that high AMR knowledge score correlated with a positive attitude towards combating AMR (p<0.001). Pharmacists had relatively higher AMR knowledge scores (mean=7.67, SD= 1.1), whereas nurses had lower scores (mean = 5.57, SD=1.9). A minority of respondents [31.5% (n=95)] indicated that poor access to local antibiogram data promoted AMR, with the majority [56.5% (n = 190)] responding that poor adherence to prescribed antimicrobials can lead to AMR. Pharmacists had the highest scores for attitude (mean=5.60, SD= 1.6) whereas nurses had the lowest scores (mean 4.02, SD= 1.4). More than half the participants (56.1%) indicated that poor adherence to antibiotics by patients promotes AMR. Conclusion: AMR knowledge and attitudes, as well as knowledge on PGx among healthcare professionals in Zambia, is sub-optimal and has potential to affect the uptake of precision medicine approaches in the future to reduce AMR rates. Educational and positive behavioural change interventions are required to address this. We will be seeking to introduce these to improve the use of antimicrobials in hospitals in Zambia in the future.